PENGARUH APLIKASI BERBASIS ANDROID AYO DEDIS UNTUK PENINGKATAN PENGETAHUAN GIZI SEIMBANG TERHADAP STUNTING PADA IBU HAMIL - LENA SEKARWATI (LPPMK STIKES Widyagama Husada, 2022)
Abstrak Sekarwati, Lena. 2021. The Effect of Android-Based Ayo Dedis Application on Increasing Knowledge of Balanced Nutrition on Stunting in Pregnant Women During a Pandemic in the Work Area of Karangploso Health Center, Malang Regency. Thesis. Nursing Study Program of Widyagama Husada School of Health. Advisors: (1) Frengki Apryanto, S.Kep., Ners., M.Kep. (2) Rosly Zunaedi, S.Kep., Ners., M.Kep. Background: Stunting may occur in mother who are too young, too old, having many birth record and short birth interval. Today is an era where everyone uses social media to interact and find information. Therefore researchers are interested in conducting research using android-based applications for prevention and early detection of pregnant women in order to reduce stunting rates and get enough information with gadgets. Objective: to examine the effect of the Android-based Ayo Dedis application on pregnant women. Methods: The effect of pregnant women's knowledge about stunting before and after using the